Exploring regional economic resilience - Edward Hill; Howard Wial; Harold Wolman (University of California, Institute of Urban and Regional Development (IURD), 2008)
Although the literature on regional macroeconomics continues to emphasize the analysis of economic growth, the concept of economic resilience is of increasing interest to policymakers. The terrorist attacks of September 11, 2001, and Hurricane Katrina in 2005 focused attention on the ability of regional economies to respond to human-made and natural disasters (Chernick 2005, Liu and Plyer 2007). The steep losses of U.S. manufacturing jobs since 2000, especially in the Great Lakes Region, have prompted a great deal of concern about how regional economies experiencing those losses can rebound (Wial and Friedhoff 2005, Wial 2007, McGahey and Vey 2008). Despite the growing importance of the idea of economic resilience, the concept has not been carefully defined or measured. Drawing on implicit definitions used in the limited literature on economic resilience and on more explicit treatments of the concept in the ecological literature, this paper begins by outlining some possible meanings of regional economic resilience. Using these definitions, it then describes in more detail a quantitative and qualitative research methodology that can be used to operationalize the concept and assess the determinants of regional economic resilience.
Keywords: 330